Cause–related marketing: uncovering the myth. (10th April 2015) - Nejati, Mehran; Amran, Azlan; Wen, Gwen Tan Yi
In accordance with companies' efforts to position themselves as socially responsible firms, the application of Cause–Related Marketing (CRM) has been growing as a helpful marketing tool. Nonetheless, there is a dearth of significant prior studies in understanding what factors influence the success of such prosocial marketing campaigns and their impacts on consumers' purchase intentions. This research attempts to investigate the influence of perceived cause importance, cause proximity, cause–brand fit and consumers' involvement in CRM on consumers' purchasing intention. Findings of the study indicate the positive and significant impact of cause importance, cause proximity, and cause–brand fit on consumers' purchase intentions, while consumers' involvement in CRM was not found to have any significant role to play. Study limitations and implications have also been outlined in the paper.